Caracterização de isolados de Serratia marcescens por whole-genome sequencing - Cruz, Thalita Priscila Peres Seabra da (2024)
Antimicrobial resistance originating from nosocomial infections ranks as the fourth leading cause of death in Brazil, and by 2050, the annual death toll worldwide could reach 10 million. The intensive and inappropriate use of antimicrobials leads to the emergence of resistance in various pathogens, reducing treatment options for infections, especially among clinically significant nosocomial agents. Serratia marcescens has become notably known for its increasing antimicrobial resistance and potential to cause outbreaks in hospital settings. The aim of this study was to establish the presence of resistance genes and virulence factors in S. marcescens strains causing an outbreak in a tertiary hospital in Cuiabá, Mato Grosso, Brazil, through Polymerase Chain Reaction (PCR) testing and subsequent Whole Genome Sequencing (WGS) for the characterization of clonal samples and outbreak confirmation. Phenotypically, the samples showed resistance to multiple drugs (MDR), being sensitive to only two antimicrobial classes out of the ten tested. Genotypically, the results indicated a variety of virulence and resistance factors, demonstrating the diversity of genetic contexts in which these genes may be inserted. Sequencing identified over 20 resistance and virulence genes such as Carbapenemases, βlactamases, aminoglycoside-hydrolyzing enzymes, and efflux pumps, detected in all samples. Due to the genotypic similarity and data obtained from WGS, it was found that the ten isolates of S. marcescens are clonal, confirming the outbreak.